School Leadership Assessment. Basic Framework in the Educational System and Regional Development - Montero Alcaide, Antonio (Avances en Supervisión Educativa, 2024)
The assessment of the school management role within the educational system is carried out through regulated frameworks which just cannot be seen as models yet. Thus, the study presented in this article intends to analyze the basic structure and evolution of these assessment procedures, as well as their current development and specification by educational administrations, so as to suggest conclusions and measures for a more suitable implementation and improvement. Therefore, numerous normative sources regarding the evaluation of leadership performance have been compared and analyzed thoroughly. The conclusions emphasize the need to clarify the fundamental nature of certain aspects of the evaluation; the variety of regional regulations, which has its own impact on the evaluation and its procedure. These conclusions also underline significant issues related to the evaluation agents, the nature of the evaluation itself, procedures, timing, dimensions, community engagement, the importance of the leadership management project or the consequences of negative evaluation outcomes.